2019
DOI: 10.1002/btm2.10136
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating plasmid nuclear delivery by interfering with the selective nuclear pore barrier

Abstract: Nuclear pore complexes (NPCs) are sophisticated transporters assembled from diverse proteins termed nucleoporins (Nups). They control all nucleocytoplasmic transport and form a stringent barrier between the cytosol and the nucleus. While selective receptor‐mediated transport enables translocation of macromolecules up to striking sizes approaching megadalton‐scale, the upper cutoff for diffusion is at 40 kDa. Raising the cutoff is of particular importance for nuclear delivery of therapeutic nanoparticles, for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The efficacy of 1,7-Hept seems to be the strongest of all three compounds, but 1,6-HD has additional advantages as it acts on another critical target, fundamental for the survival of cancer cells, namely, nuclear pore complexes, as demonstrated in our recent studies. [20,39] Furthermore, the molecular structure of 1,5-PD, 1,6-HD, and 1,7-Hept follows the "Lipinski rule of five" for drug design [40] (Table S1, Supporting Information), which may qualify them as promising molecules for clinical applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of 1,7-Hept seems to be the strongest of all three compounds, but 1,6-HD has additional advantages as it acts on another critical target, fundamental for the survival of cancer cells, namely, nuclear pore complexes, as demonstrated in our recent studies. [20,39] Furthermore, the molecular structure of 1,5-PD, 1,6-HD, and 1,7-Hept follows the "Lipinski rule of five" for drug design [40] (Table S1, Supporting Information), which may qualify them as promising molecules for clinical applications.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of 1,7‐Hept seems to be the strongest of all three compounds, but 1,6‐HD has additional advantages as it acts on another critical target, fundamental for the survival of cancer cells, namely, nuclear pore complexes, as demonstrated in our recent studies. [ 20,39 ]…”
Section: Resultsmentioning
confidence: 99%
“…At concentrations applied in the present work, the utilized compounds do not dissociate FG‐Nups from the NPC barrier but interfere with their mutual bonds and consequently relax the barrier, as reported in our recent publications. [ 48 , 49 ] We used time‐lapse video microscopy to observe highly metastatic A549_3R cells over a time interval of 10 h whereby they were exposed to 2% (m/v) of either NPC barrier breakers 1,2‐trans‐Cyclohexanediol (1,2‐TCHD), 1,6‐Hexanediol (1,6‐HD), in combination (1% each), or their negative controls 1,4‐Cyclohexanediol (1,4‐CHD) and 1,2,3‐Hexanetriol (1,2,3‐HT), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We know from our previous publications that the NPC barrier breakers utilized in the present work at specified concentrations, do not dissociate FG‐Nups from the NPC barrier but rather disrupt their crucial interaction with each other and consequently prevent their selective barrier function. [ 48 , 49 ] How can interference with the NPC barrier have such profound impact on the overall structural and dynamical properties of cells? The NPCs are turnstiles of nucleocytoplasmic crosstalk.…”
Section: Resultsmentioning
confidence: 99%
“…1,6-HD, an aliphatic alcohol, specifically disrupts multivalent hydrophobic interactions between protein-RNA or protein-protein that are favorable to the formation of LLPS [10,19,20]. It has been reported that 1,6-HD affects cell viability in HeLa cells while the cytotoxicity of 1,6-HD on EA.hy926 cells is minimal [21,22]. Therefore, it is plausible to reason 1,6-HD may have function in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%